2020
DOI: 10.1001/jama.2020.7848
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Statin Use With All-Cause and Cardiovascular Mortality in US Veterans 75 Years and Older

Abstract: IMPORTANCE Data are limited regarding statin therapy for primary prevention of atherosclerotic cardiovascular disease (ASCVD) in adults 75 years and older.OBJECTIVE To evaluate the role of statin use for mortality and primary prevention of ASCVD in veterans 75 years and older. DESIGN, SETTING, AND PARTICIPANTSRetrospective cohort study that used Veterans Health Administration (VHA) data on adults 75 years and older, free of ASCVD, and with a clinical visit in 2002-2012. Follow-up continued through December 31,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
130
0
6

Year Published

2020
2020
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 173 publications
(159 citation statements)
references
References 38 publications
2
130
0
6
Order By: Relevance
“…Prior HIV cohort analyses have reported a disproportionately large statin-associated mortality bene t of > 50% [9][10][11] which resembles reports of ≥ 40% reduced mortality among statin users in other populations with altered immunity [27][28][29], inherently increased (cardiovascular) mortality risk [30][31][32][33], or old age (25% mortality reduction in men > 75 years) [34]. Decreased mortality had never been observed in primary NS-LLT prevention trials but has recently been reported when icosapent-ethyl ( sh oil component) or alirocumab (PSK-9 inhibitor) was added to statins in high-risk populations [35,36].…”
Section: Discussionmentioning
confidence: 96%
“…Prior HIV cohort analyses have reported a disproportionately large statin-associated mortality bene t of > 50% [9][10][11] which resembles reports of ≥ 40% reduced mortality among statin users in other populations with altered immunity [27][28][29], inherently increased (cardiovascular) mortality risk [30][31][32][33], or old age (25% mortality reduction in men > 75 years) [34]. Decreased mortality had never been observed in primary NS-LLT prevention trials but has recently been reported when icosapent-ethyl ( sh oil component) or alirocumab (PSK-9 inhibitor) was added to statins in high-risk populations [35,36].…”
Section: Discussionmentioning
confidence: 96%
“…However, in this meta-analysis, statin therapy did not reduce the vascular events, including recurrent ischemic stroke, acute coronary events, and MACE. Recent cohort studies involving older adult participants without atherosclerotic cardiovascular disease have reported that statin treatment has a major advantage for mortality over prevention of ischemic stroke or myocardial infarction ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among US Veterans above the age of 75, one study found that initiation of statin therapy for primary prevention significantly reduced all-cause and cardiovascular mortality [36]. This study retrospectively analyzed 326,981 veterans (average age 81.1, of which 97% were men and 91% were white).…”
Section: Mortalitymentioning
confidence: 99%